Diagnosis and treatment of ectopic thyroid carcinoma: A case report and literature review - Fu, Guiming; Guo, Fengli; Zhang, Wei; Ruan, Xianhui; Zheng, Xiangqian; Wang, Zhaohui; Gao, Ming (Frontiers in Oncology, 2022)
Introduction Ectopic thyroid cancer (ETC) is primary thyroid cancer occurring in ectopic thyroid tissue, and its incidence rate is approximately 0.3%–0.5% of thyroid cancer. Only approximately 132 cases of ETC have been diagnosed and treated worldwide in the past 110 years, with most of them being adults. Of note, patients with ETC are prone to misdiagnosis and mistreatment. Case report This was a 13-year-old adolescent female who reported having a sensation of swallowing obstruction when eating blocky foods. Color Doppler Ultrasound (CDU) found a 2.3 cm ×1.7 cm × 2.1 cm hypoechoic nodule slightly to the right of the deep surface of the tongue base, with a honeycomb shape. Meanwhile, a mixed echogenic nodule of approximately 2.0 cm × 1.9 cm × 2.3 cm was seen deep in the mouth floor, and a very low echogenic region of 1.4 cm × 1.1 cm × 1.8 cm was observed in the nodule. We then performed a fine needle aspiration biopsy (FNAB) of the thyroid nodules guided by CDU, and the results showed papillary thyroid carcinoma (PTC). Then, a local extended resection of the thyroid carcinoma was performed. Bilateral cervical IA and adjacent subhyoid lymph node dissection was performed through a small anterior cervical incision. The patient recovered well, and was discharged on the fifth day after surgery. The patient only took levothyroxine tablets for replacement therapy after surgery. The patient was followed up for 36 months, and the thyroid function remained in the normal range. Reexamination by CDU showed no tumor recurrence, lymph node enlargement, or obvious change in the tongue base ectopic thyroid. Conclusions ETC is an extremely rare type of thyroid cancer, which is easy to be misdiagnosed. Preoperative use of CDU, nuclide scanning, computed tomography (CT)/Magnetic resonance imaging (MRI), and FNAB can significantly reduce the misdiagnosis rate of this disease. Surgery is currently the main treatment for ETC. Complete resection still has a high cure rate. For patients with advanced ETC who cannot be completely resected, external radiotherapy and targeted therapy can be tried, but the prognosis needs to be verified with more cases in the future.